Evaluation of the Effects of Punica granatum Flower Tablets on Pain and Healing of Minor Recurrent Aphthous Stomatitis: A Randomized Clinical Trial - Fatemeh Lavaee; Elahehnaz Parhizkar; Fatemeh Tavakoli; Mohammad M. Zarshenas; Naeimehossadat Asmarian (Wiley, 2024)
ABSTRACT Objectives The purpose of this study was to determine the therapeutic effect of the Punica granatum (PG) flower on recurrent aphthous stomatitis in comparison with corticosteroid therapy. Materials and Methods This cross‐over randomized clinical trial was conducted on the patients who had been referred to Shiraz Dental School for their RAS in 2021. All the participants used both P. granatum flower tablets and Triadent a month apart for wash‐out time and all compared themselves. In the experimental group, 30 patients received pomegranate flower tablets, three tablets daily, for 6 days. In the control group, oral paste Triadent has been prescribed three times a day for 6 days. The visual analog scale (VAS) and the size of RAS were evaluated on Days 0-6. Data were analyzed by SPSS version 21. The Wilcoxon test was used. Results The mean age of participants was 27.8 ± 14.77 years old. In this study, 15 patients (50%) were men and 15 patients (50%) were women. The mean value of VAS after using prescribed treatment in both evaluated groups on all days was significantly different such that the VAS values were lower for PG flower tablets than Triadent (p value < 0.05). The size of oral lesions in participants who used PG flower tablets was significantly less than those who used Triadent on all evaluation days (p value < 0.05) except on Day 1 (p value = 0.29). The descending slope of VAS from Days 1 to 6 for both Triadent and PG flower tablet users was significant and noticeable. (p value < 0.05). Conclusion According to the result of this study, both P. granatum flower tablet and Triadent are useful in reducing the size, period of healing, and VAS of patients with RAS, but the PG flower tablet is more effective.